2013
DOI: 10.1073/pnas.1312065110
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress activation of nuclear receptor PXR in endothelial detoxification

Abstract: Endothelial cells (ECs) are constantly exposed to xenobiotics and endobiotics or their metabolites, which perturb EC function, as well as to shear stress, which plays a crucial role in vascular homeostasis. Pregnane X receptor (PXR) is a nuclear receptor and a key regulator of the detoxification of xeno-and endobiotics. Here we show that laminar shear stress (LSS), the atheroprotective flow, activates PXR in ECs, whereas oscillatory shear stress, the atheroprone flow, suppresses PXR. LSS activation of PXR in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…A number of studies have reported that Abcb1 gene expression can be regulated by various factors such as steroid hormones (Nuessler et al 1997, Nakayama et al 1999, cellular membrane stretch (Sardini et al 1994, Wang et al 2013, and inflammation (Salkeni et al 2009, Poller et al 2010, Gibson et al 2012. P4 is the major regulatory hormone of pregnancy, essential for the maintenance of pregnancy and uterine growth (Thijssen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that Abcb1 gene expression can be regulated by various factors such as steroid hormones (Nuessler et al 1997, Nakayama et al 1999, cellular membrane stretch (Sardini et al 1994, Wang et al 2013, and inflammation (Salkeni et al 2009, Poller et al 2010, Gibson et al 2012. P4 is the major regulatory hormone of pregnancy, essential for the maintenance of pregnancy and uterine growth (Thijssen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Through PXR activation vascular tissue was able to convert the inactive pro-drug clopidogrel to its active metabolite [5]. A number of these findings were recently confirmed in vitro and in vivo [40] and extended to show that PXR activity is up-regulated in regions of laminar shear stress (athero-protected) but depressed with oscillatory shear stress (proatherogenic) in the mouse [40].…”
Section: Xenobiotic Receptorsmentioning
confidence: 80%
“…98 Recently, the IL-8 receptor (IL8R), also known sion of proinflammatory adhesion molecules, such as vascular cell adhesion molecule-1 (VCAM-1) and endothelial leukocyte adhesion molecule-1 (ELAM-1, otherwise known as E-selectin) in response to tumor necrosis factor-α (TNF-α) and lipopolysaccharide (LPS) in ECs. 53 Overexpression of a constitutively active PXR in rat carotid arteries also potently attenuated proinflammatory responses. 53 PXR is also expressed in classical immunocytes including monocytes/macrophages and lymphocytes (both T and B cells) and inhibits inflammation.…”
Section: Ahr and Vascular Diseasementioning
confidence: 99%
“…17 The circulation can be a hostile milieu, with increased concentrations of xenobiotics and endobiotics resulting from drugs, chemical agents, smoking, air pollution, nutritional metabolites, and pathogenic microbes or their toxins. 53 These circulating endogenous and foreign chemicals can contribute to vascular dysfunction and the development of vascular disease. 54 Recent studies have demonstrated that PXR is not only expressed in the liver and intestine and its role in detoxification is not liver and intestine specific.…”
Section: Pxr and Car In Drug Metabolismmentioning
confidence: 99%